This beautiful life [large type]: a novel - Schulman, Helen (Thorndike Press large print core series., 2011)
When the Bergamots move from an upstate college town to New York City, they're not sure how they'll adapt. Soon Richard is consumed by his executive role at a large university. Liz, who gave up an academic career to raise her children, is busy ferrying young Coco around. And fifteen-year-old Jake is taken into the fold at an elite private school. But their upper class cocoon is ripped apart by scandal when Jake causes a good family to face bad choices. Bestseller